PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA GOL I BAGI DIRI SENDIRI (PUTUSANNO.522/PID.SUS/2021/PN MGL): Punishment of the perpetrators of the crime of drug abuse category I for themselves (Decision Number 522/Pid.Sus/2021/PN MGL) - Wennora, Febrezi; Syahputra, Azmi (Faculty of Law, Universitas Trisakti, 2024)
Narcotics crimes have various kinds of sanctions that can be imposed on the perpetrator, one of which is the crime of abusing narcotics for oneself. In this case, the most appropriate sanction for perpetrators of narcotics abuse for themselves is action sanctions in the form of rehabilitation sanctions. However, often perpetrators of criminal acts of narcotics abuse for themselves are considered to be narcotics dealers because there are still no clear boundaries regarding the boundaries between the actions committed by narcotics abusers for themselves and narcotics dealers. For example, in the case where the defendant Hendra bin Zainuri committed a class 1 narcotics abuse crime for himself in Decision No. 522/Pid.Sus/2021/PN Mgl, it was decided under Article.